AI-Based Personalization and Consumer Purchase Intention: Examining the Effects of Social Media Engagement and Digital Content Quality - Jaemi Wahyudi; Mohammad Rafii; Bayu Suratmoko; Ahyar Junaedi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This study examines the influence of AI-Based Personalization (ABP), Social Media Engagement (SME), and Digital Content Quality (DCQ) on students’ Purchase Intention (PI) in the context of AI-based digital marketing. The study employed a quantitative approach using explanatory research and Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis with SmartPLS. A total of 227 students from Universitas Muhammadiyah Palangkaraya were selected through purposive sampling. The measurement model evaluation indicated that all indicators were valid and reliable, with outer loading values above 0.70, Composite Reliability above 0.70, and AVE above 0.50. The structural model showed moderate predictive capability with an R-square value of 0.430 and Q²predict value of 0.384. Hypothesis testing revealed that SME positively and significantly influenced PI (β = 0.329; T = 4.610; P = 0.000), while DCQ also had a positive and significant effect on PI (β = 0.323; T = 3.931; P = 0.000). However, ABP had no significant effect on PI (β = 0.104; T = 1.312; P = 0.189). The findings indicate that social media engagement and digital content quality are more influential in increasing students’ purchase intention than AI-based personalization.